(untitled) (Bangladesh Journal of Urology, 2023)
Background: The objective of this study is to observe the frequency of prostate cancer detected by TRUS guided prostate biopsy in patients with serum PSA 4-10 ng/ml. Methods: Patients aged 50-80 years were entered this study and 46 patients with serum PSA level 4-10 ng/ml underwent TRUS guided 12 cores systematic biopsy. Results: The mean age of the patients was 63.1 (±10.0) years. All of them had serum PSA level 4-10 ng/ml and the mean PSA was 6.9 (±1.4) ng/ml. On digital rectal examination (DRE) hard nodule was found in 4 (8.7%) patients, among them 3 (42.9%) patients had malignant lesion and 1 (2.6%) patient had non-malignant lesion, that was statistically significant (P=0.009). A total 7 (15.2%) patients had malignant lesion on histopathology, all of them were adenocarcinoma, 5 (71.4%) patients had Gleason’s score ≤ 6 while 2 (28.6%) patients had Gleason’s score 7. The result was statistically significant. Conclusion: This study concluded that, the overall detection rate of prostate cancer in Bangladesh was 15.2% with the diagnostic gray zone of serum PSA from 4 to 10 ng/ml. TRUS guided prostate biopsy had become a widely accepted and routinely performed technology to detect PCa. Bangladesh J. Urol. 2023; 26(1): 33-39